(3GdCbhGd GdegeI aj CMcGe Cgd GdPeI ddaGcgis - (3eMeO Hf ESMGb Hf GdYHGS GdaGcgj,J (B272 (3g` s ((3YHjO Gddg Hf eMeO Hf YHO Gddg GdYeQGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CeJfi YdjfG HGdESdGe hHYO abO hQO Ydi Ydi SDGd Yf EjVGM eTcd YQV aSOOJ SgGe GdacQ Edjg QLG Cf jUjH GdZQV s
(3BNQgG (B:s
(3hCXgQ GdCbhGd ai GdbjGS bhd eLGgO heJGHYjg Efge djShG Ydi Ojf GdjghO hGdfUGQi Je GdLhGH hGddg GdgGOi Edi GdUhGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B28s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs